A harmonious relationship of religion and science: muslim intellectual responses - Abdul Rahim, Adibah (2006)
The perception of Muslim thinkers toward science can be divided into two main groups. The first group advocated confrontation and rejection of science. The claimed science to be a product of the West and thus, perceived it as incompatible with Islam. As opposed to this antagonistic attitude towards science, the second group stressed on the harmonious relationship of religion and science. This is one of the most fundamental issues raised by Muslim modernists to overcome the major intellectual problem of compartmentalization of knowledge, and so sought to bridge the gap between the traditional learning and modern sciences. The author emphasizes that the dichotomy between religion and science is due to a misunderstanding of what science is and the misapplication of science itself. The separation between religion and science should not continue since both are complimentary ways of understanding reality. Therefore, there is a need to find points of agreements between religion and science. This paper aims at analyzing the Muslim intellectual responses as embodied in the ideas and works of prominent 19th and 20th centuries Muslim thinkers who demonstrated a systematic approach and offered mechanisms for building of coherent view of the harmonious relationship of religion and science.